2007
DOI: 10.1038/oby.2007.292
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Breakfast Consumption and Weight Gain among U.S. Men

Abstract: Results: Overall, 5857 men had a weight gain of 5 kg or greater during 10 years of follow-up. Breakfast consumption was inversely associated with the risk of 5-kg weight gain after adjustment for age [hazard ratio (HR) ϭ 0.77 (95% confidence interval [CI], 0.72 to 0.82)], and this association was independent of lifestyle and BMI at baseline [HR ϭ 0.87 (95% CI, 0.82 to 0.93)]. Fiber and nutrient intakes partially explained the association between breakfast consumption and weight gain. The inverse association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
145
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(160 citation statements)
references
References 31 publications
7
145
2
6
Order By: Relevance
“…Eating patterns that may influence body weight include eating frequency, [11][12][13] breakfast skipping [12][13][14][15][16][17][18] and the frequency of meals eaten away from home. 12 Among these, breakfast skipping has received a lot of attention recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eating patterns that may influence body weight include eating frequency, [11][12][13] breakfast skipping [12][13][14][15][16][17][18] and the frequency of meals eaten away from home. 12 Among these, breakfast skipping has received a lot of attention recently.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] A prospective study also found that skipping breakfast was associated with weight gain. 16 However, others have found contradictory results regarding the association of breakfast skipping with body mass index (BMI), 17 or with overweight/obesity. 18 The discrepancy may be due to differences in the definitions of breakfast skippers among studies.…”
Section: Introductionmentioning
confidence: 99%
“…Some cross-sectional (5)(6)(7)(8) and a few longitudinal (9,10) studies have addressed the association between BMI and lifestyle factors. Among them, breakfast consumption habits have been shown to be strongly related to overweight and obesity (6,(11)(12)(13) . In addition, persons who consume lowenergy breakfast or no breakfast at all have been shown to have higher cholesterol levels, and this applies to both adults and children (14) .…”
mentioning
confidence: 99%
“…However, several methodological limitations make it difficult to interpret these studies. First, EF has often been estimated using a series of self-report questions (8)(9)(10)(11)(15)(16)(17)(18)(19) , the validity of which has not been examined or reported. Only a limited number of studies have estimated EF with the use of information on actual dietary behaviours (based on dietary record or 24 h recall) (20)(21)(22)(23)(24) .…”
mentioning
confidence: 99%
“…Second, there is no consensus about what constitutes a snack, a meal or an eating occasion. While some studies have relied on respondents' self-identification of meals, snacks or eating occasions (8)(9)(10)(11)(15)(16)(17)(18)25,26) , others have tried to apply more objective criteria (19)(20)(21)(22)(23)(24)(27)(28)(29)(30) . Third, the associations between EF and dietary intake may be confounded by the under-reporting of EF accompanied by the under-reporting of energy intake (EI), particularly by obese or overweight individuals (12,13) .…”
mentioning
confidence: 99%